OP07 Effect of Socio-economic Status on Risk of Colorectal Cancer in Australia. (13th September 2016) - Jongcherdchootrakul, K; Flander, L; English, DR; Giles, GG; Jenkins, MA; Ouakrim, DA
Abstract : Background: Australia has the highest colorectal cancer incidence in the world. It is the second leading cause of cancer death in both sexes. Australians in the lowest socio-economic categories generally have shorter life expectancy with greater mortality and morbidity rates from illnesses. No contemporary longitudinal studies have investigated the association between socio-economic status and risk of colorectal cancer in the Australian context. The aim of our analysis is to address this gap and provide precise estimates of this association. Methods: 39, 149 participants of The Melbourne Collaborative Cohort Study (MCCS) were included in the analysis. All participants were free from colorectal cancer at baselines (1991–1995) and were followed up at 5 and 10 years since recruitment. During overall 423, 234 person-years of observation, 1, 175 carriers (3.0%) were diagnosed with colorectal cancer. We used Cox proportional hazards regressions to estimate hazards ratios (HRs) and 95% confidence intervals (CIs) for the associations between Index of Relative Socio-economic Disadvantage, education level and country of birth, and risk of colorectal cancer. All incident colorectal cancer cases were identified through the Victorian Cancer Registry and the National Cancer Statistics Clearing House. Results: People living in the least disadvantaged areas were 30% (HR: 0.70, 95% CI: 0.49–0.99) less likely to develop colorectal cancer compared to those living in the most disadvantage areas. Moreover, Participants born overseas were 31% (HR: 0.69, 95% CI: 0.59–0.83) less likely to develop colorectal cancer compared to those born in Australia. There was no evidence for an association between education level and risk of colorectal cancer in this study. Conclusion: In this study, we found evidence that lower socio-economic status is strongly associated with greater risk of developing colorectal cancer. This is consistent with findings from the United States and Europe. Most importantly, our results highlight a major inequity issue in the current colorectal cancer prevention policies in Australia and the urgent need for targeted strategies the address the higher colorectal cancer risk faced by those in the most vulnerable segments of the population.